2019
DOI: 10.1016/j.aop.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and speed of evolution for a spin-s system with long-range zz-type Ising interaction

Abstract: We study the evolution of a spin-s system described by the long-range zz-type Ising interaction. The Fubini-Study metric of the quantum state manifold defined by this evolution is obtained. We explore the topology of this manifold and show that it corresponds to a sphere. Exploration of the Riemannian curvature allows us to determine the manifold geometry. Also we calculate the speed of evolution of the system and represent the curvature by means of this speed. This is important for an experimental measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…As we can see, the closer the angle θ is to the value π/2 and 3π/2, the more accurate the quantum computer performs the measurements. This fact follows form definition of the U (θ, φ, λ) gate (17). In general case, this gate is performed by five basis operators.…”
Section: B Distance Between Schrödinger Cat and Factorized Statesmentioning
confidence: 71%
See 1 more Smart Citation
“…As we can see, the closer the angle θ is to the value π/2 and 3π/2, the more accurate the quantum computer performs the measurements. This fact follows form definition of the U (θ, φ, λ) gate (17). In general case, this gate is performed by five basis operators.…”
Section: B Distance Between Schrödinger Cat and Factorized Statesmentioning
confidence: 71%
“…The concept of a distance between quantum states in Hilbert space [1][2][3] has found its application in different fields of quantum mechanics related to the evolution of quantum systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], quantum entanglement [8,[20][21][22][23][24][25][26][27][28][29][30], quantum computations [31][32][33][34][35], etc. It was shown that the distance, which the quantum system passes during the evolution in the Hilbert space, is related to the integral of the uncertainty of energy that in turn defines the speed of evolution [4].…”
Section: Introductionmentioning
confidence: 99%